INFLUENCE OF SHOCK WAVES ON THE LIGHT CURVES OF LONG-PERIOD VARIABLES - Kudashkina, L. S.; Rudnitskij, G. M. (Одеські астрономічні публікації, 2017)
The shapes of light curves of Mira-type variable stars is analyzed. It is shown that some features of the light curves may be explained by passage of shock waves in the stars' atmospheres. In particular, it is noted that "steps" of the ascending branches of the light curves have very similar durations (of the order of 0.1 stellar period) for a big number of miras. This time span is just approximately the time of propagation of shock waves through stars' atmospheres. The numerical simulation of shock wave propagation support the above suggestion and yield time scales that fit the observed light curve features.